2021
DOI: 10.1186/s13244-021-00998-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the CO-RADS and the RSNA chest CT classification system concerning sensitivity and reliability for the diagnosis of COVID-19 pneumonia

Abstract: Background The Radiological Society of North America (RSNA) recently published a chest CT classification system and Dutch Association for Radiology has announced Coronavirus disease 2019 (COVID-19) reporting and data system (CO-RADS) to provide guidelines to radiologists who interpret chest CT images of patients with suspected COVID-19 pneumonia. This study aimed to compare CO-RADS and RSNA classification with respect to their sensitivity and reliability for diagnosis of COVID-19 pneumonia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…In two other studies, according to the RSNA expert consensus statement, it has been reported that interobserver agreement varies between good and excellent (K = 0.822–0.924). In both studies, interobserver agreement was found to be significantly high in typical and negative categories for RSNA, whereas it was found to be poor or moderate in indeterminate and atypical categories [ 24 , 25 ]. In these studies, the high number of patients in the negative category for RSNA may have led to a partial increase in interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
“…In two other studies, according to the RSNA expert consensus statement, it has been reported that interobserver agreement varies between good and excellent (K = 0.822–0.924). In both studies, interobserver agreement was found to be significantly high in typical and negative categories for RSNA, whereas it was found to be poor or moderate in indeterminate and atypical categories [ 24 , 25 ]. In these studies, the high number of patients in the negative category for RSNA may have led to a partial increase in interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid spread of the COVID-19 pandemic, the development of a standardized score with fixed criteria is essential to improve the consistency of the interpretations of chest CT images among radiologists [ 13 , 14 ]. Regarding the complexity and time-consuming application of the current scores in clinical practice, we hypothesized a simple score that is a simplification of a well-known current chest CT score.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of evidence has enabled radiologists to classify imaging findings by different specificities and establish standard reporting and CT categorization systems based on the probability of COVID-19 [ 48 ]. To date, four major systems have been proposed as summarized in Table 1 [ 49 ].…”
Section: Standard Reporting System Of Covid-19 Pneumoniamentioning
confidence: 99%